Clinical characteristics of scleroderma overlap syndromes: comparisons with pure scleroderma. (29th April 2016) - Foocharoen, Chingching; Netwijitpan, Sittichai; Mahakkanukrauh, Ajanee; Suwannaroj, Siraphop; Nanagara, Ratanavadee
Abstract: Background: Scleroderma with characteristics of other connective tissue diseases is called scleroderma overlap syndrome (SOV); the clinical features of which have yet to be investigated among Thai patients. Objective: To determine the clinical differences between pure scleroderma and SOV. Methods: A historical cohort study was conducted among patients with pure scleroderma versus those with SOV. Subjects were over 18 years of age and followed up at Srinagarind Hospital, Khon Kaen University, Thailand, between January 2006 and December 2011. Results: Four hundred and three medical records were included (276 female vs . 127 male). SOV was found in 68 cases (16.9%): (i) scleroderma–polymyositis overlap (SOV‐PM), the most common type of SOV (48 cases; 70.6%); (ii) scleroderma–systemic lupus erythematosus overlap (11 cases; 16.2%); and (iii) scleroderma–rheumatoid arthritis overlap (nine cases; 13.2%). Mean age at onset of non‐systemic sclerosis symptoms was 46.9 ± 11.8 years (range, 19.8–74.3). Characteristically, sufferers of SOV as against pure scleroderma were younger, had less frequent anti‐topoisomerase I (ATA) and needed moderate‐ to high‐dose steroid and immunosuppressant therapy during follow‐up. SOV‐PM presented the clinical features of scleroderma at onset and during follow‐up looks like pure scleroderma having vasculopathy, severity of skin tightness, and gastrointestinal, cardiopulmonary and renal involvement. Anti‐Ro52 was the most common serology among sufferers of SOV (31.6%). ATA was associated with pure scleroderma patients ( P = 0.047). Conclusions: SOV rather than pure scleroderma presented in younger Thai scleroderma patients and SOV‐PM was the most common subtype and its clinical features were similar to those of pure scleroderma. ATA was strongly associated with the latter.